HUBUNGAN POLA ASUH ORANG TUA DAN RASA PERCAYA DIRI ANAK PADA PAUD AR-RAHMAN JALAN RONGGOSUKOWATI NO. 55 KOLPAJUNG KECAMATAN PAMEKASAN KABUPATEN PAMEKASAN TAHUN PELAJARAN 2021/2022 - Yesita Tria Arisanti; Wahono Wahono; Naili Saâ€™ida (PROCEEDING UMSURABAYA, 2022)
The purpose of this study was to determine the relationship between parenting styles and children's self-confidence at Ar-Rahman Early Childhood Education, Jalan Ronggosukowati No. 55 Kolpajung, Pamekasan District, Pamekasan Regency for the 2021/2022 Academic Year. Every child basically has self-confidence, although in different fields and levels. This potential requires stimulation from an early age. Confidence is an important thing that every child must have to step on the wheel of life. A child's strong mentality and character will be important capital for their future when they reach adulthood, so they are able to respond. The research method used in this research is quantitative. With data collection techniques by observation, interviews, documentation. Data analysis used is data analysis by weighing, filtering, and regulating and classifying data. The results obtained in this study are that there is a relationship between parenting patterns and children's self- confidence at PAUD Ar-Rahman Jalan Ronggosukowati No. 55 Kolpajung, Pamekasan District, Pamekasan Regency for the 2021/2022 Academic Year, with a high correlation level.Â Keywords: parenting; parents; early age; potential